Synthesis of novel graphene oxide/bentonite bi-functional heterogeneous catalyst for one-pot esterification and transesterification reactions - Ali, B. (Elsevier Ltd, 2018)
Several heterogeneous catalysts have been utilized for biodiesel synthesis from low-grade oils containing free fatty acids (FFA) in a two-stage esterification and transesterification method in previous studies. In this study, NaOH-bentonite impregnated with graphene oxide (GO), as a novel bi-functional heterogeneous catalyst for simultaneous esterification and transesterification was developed and characterized by thermogravimetric analysis (TGA), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, field emission scanning electron microscopy (FESEM), N2 adsorption measurement to obtain the surface area (BET) and temperature programmed desorption (TPD NH3 and CO2). The effect of reaction time (h), reaction temperature (Â°C), methanol-to-oil ratio and catalyst amount (wt) was studied. All experiments were performed at an optimized GO-to-NaOH-bentonite ratio of 1:20. Impressively, the GO-NaOH-bentonite catalyst exhibited excellent catalytic performance and resulted in 89.5 wt conversion of free fatty acids and 98.5 wt overall biodiesel yield after 4.5 h reaction time with catalyst amount of 6 wt, reaction temperature of 62 Â°C and 6:1 methanol-to-oil ratio. Results showed that the presence of Na2O enhanced the low-strength basic sites of the catalyst at 150â200 Â°C, which played the key role in transesterification of rapeseed oil. It was also found that, the presence of GO on NaOH-bentonite, increased the overall acid strength of the composite catalyst by providing more BrÃ¸nsted acidic sites. The acidic-basic nature of GO-NaOH-bentonite improved the accessibility of methanol to oil and FFA with the increased pore size of the composite catalyst. Â© 2018 Elsevier Ltd